The Effects of Risk Management on Performance of Euro Mediterranean Insurance Firms - Attard Maria; Caruana Yanica; Dalli Gonzi Rebecca; Galea Chantelle; Girlando Alessandra; Grech Janice; Soar Aliscia; Teuma Joseph; Daniela Vella; Simon Grima (International Business and Accounting Research Journal, 2021)
The aim with this paper is to show the differences in the performance of eight insurance companies in the Mediterranean region and how each country deals with risks. Risk management is crucial in insurance companies because if risks are not mitigated, the company will suffer financial losses and poor performance within the company. With the introduction of the Solvency II Directive, consumer protection is improved by law at European Union. This paper shows the steps of risk management and comparison of these eight Mediterranean countries before the Solvency II directive and after it came into force. The eight Mediterranean countries are Spain, France, Greece, Cyprus, Italy, Slovenia, Malta and Croatia and the economy of each country and the economy of insurance is presented. The aim of this study is to examine the different risk management practices adopted by insurance companies and how risk management affects the performance of insurance companies in these countries, as well as the relationship between risk management and insurance.